2020
DOI: 10.1002/jhbp.767
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cholecystitis after stent placement in patients with distal malignant biliary obstruction

Abstract: Background /PurposeLimited data are available for acute cholecystitis after Self‐Expandable Metallic Stent (SEMS) placement in patients with malignant distal biliary obstruction. We aimed to identify risk factors for cholecystitis.MethodsThis was a retrospective, single‐center study of 280 patients (336 stents) who received endoscopic SEMS placement between May 2005 and April 2016. Clinical records were used to perform risk factor analyses.ResultsOf 336 SEMS placement procedures, 25 (7.4%) led to development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…POEC-CL has been explored in an initial proof-of-concept series of 5 to 25 cases, with a very high rate of technical success (88%-100%) and a low rate of adverse events (0%-3.84%). [6][7][8][9][10][11] This possibility pushes EUS-GBD beyond AC palliation in patients unfit for surgery, offering a potentially "curative" option in all patients in whom surgery is undesirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POEC-CL has been explored in an initial proof-of-concept series of 5 to 25 cases, with a very high rate of technical success (88%-100%) and a low rate of adverse events (0%-3.84%). [6][7][8][9][10][11] This possibility pushes EUS-GBD beyond AC palliation in patients unfit for surgery, offering a potentially "curative" option in all patients in whom surgery is undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, AC might be an expected adverse event of local cancer invasion or palliative procedures (eg, SEMS placement). 7,8 An eventual surgical treatment can expose these patients to a discontinuation or delay in chemotherapy that could significantly affect their prognosis. In another elderly, frail, and comorbid patient with a severe form of myeloprolierative disease, the procedure resulted in a dramatic improvement of severe septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Takinami et al reported that CSEMS is an important risk factor of acute cholecystitis. 18 Acute cholecystitis development needs some intervention procedures, such as cholecystectomy or percutaneous drainage, which could be fatal. Isayama et al previously described that cholecystitis development is not related to the type of metallic stent but the presence of tumor invasion into the cystic duct orifice.…”
Section: Discussionmentioning
confidence: 99%
“…Takinami et al . reported that CSEMS is an important risk factor of acute cholecystitis 18 . Acute cholecystitis development needs some intervention procedures, such as cholecystectomy or percutaneous drainage, which could be fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive cholecystitis may complicate around 15 % of SEMS placements [2]. Its occurrence seems unrelated to whether the SEMS is covered or uncovered [3], and to be favored by neoplastic infiltration of the cystic duct [2,4]. Although E-Videos ▶ Fig.…”
mentioning
confidence: 99%